Role of Translocator 18 KDa Ligands in the Activation of Leukotriene B4 Activated G-Protein Coupled Receptor and Toll Like Receptor-4 Pathways in Neutrophils - Kupa, Léonard de Vinci Kanda; Drewes, Carine C.; Barioni, Eric D.; Neves, Camila L.; Sampaio, Sandra Coccuzzo; Farsky, Sandra H. P. (Frontiers in Pharmacology, 2017)
TSPO (Translocator 18KDa; tryptophan-rich sensory protein oxygen sensor) is a constitutive outer mitochondrial membrane protein overexpressed in inflammatory cells during local or systemic processes. Despite its expression is characterized, role of TSPO in inflammation remains elusive. For this study, we investigated the role of TSPO ligands on neutrophil functions elicited by two different inflammatory pathways. Peritoneal neutrophils were isolated from male Balb-C mice, treated with TSPO ligand diazepam, Ro5-4864 or PK11195 (1,100 or 1000nM; 2 hours) and further stimulated with lipopolysaccharide from Escherichia coli (LPS), a binding for Toll-Like Receptor-4 (TLR4), or leukotriene B4 (LTB4), a G-protein coupled receptor (GPCR) ligand. LPS treatment did not lead to overexpression of TSPO on neutrophils, and pre-treatment with any TSPO ligand did not alter cytokine expression, adhesion molecule expression, or the production of reactive oxygen and nitrogen species caused by LPS stimulation. Conversely, all TSPO ligands impaired LTB4’s actions, as visualized by reductions in L-selectin shedding, β2 integrin overexpression, neutrophil chemotaxis, and actin filament assembly. TSPO ligands showed distinct intracellular effects on LTB4-induced neutrophil locomotion, with diazepam enhancing cofilin but not modifying Arp2/3 expression, and Ro5-4864 and PK11195 reducing both cofilin and Arp2/3 expression. Taken together, our data exclude a direct role of TSPO ligands in TLR4-elicited pathways, and indicate that TSPO activation inhibits GPCR inflammatory pathways in neutrophils, with a relevant role in neutrophil influx into inflammatory sites.